SCREENING OF RESPONSES OF ADULT KHAPRA BEETLE, TROGODERMA GRANARIUM E. ON TEN PLANTS SPECIES FOR POSSIBLE REPELLENT ACTION - MARGARAT, A.; JAGADEESAN, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
Penicillamine is also one of the antidote for heavy metal poisoning. The sub-lethal dose of mercuric chloride on carbohydrate metabolism in mice results in an initial increase and concomitant decrease of glycogen content in brain and liver tissues respectively. The glucose content shows decreased level in all tissues (brain, liver, muscle and kidney) to meet extra energy demand due to mercury toxicity. Antidote shows a remarkable recovery on carbohydrate metabolism in mercury toxicated mice.